Self-Enforcing International Environmental Agreements and Altruistic Preferences - Mark Schopf (Environmental and Resource Economics, 2024)
This paper analyses the effects of altruism on the formation of climate coalitions in the standard two-stage game of self-enforcing international environmental agreements with identical countries. Altruism implies that each country values, to some extent, every other country's welfare when deciding on its coalition membership and emissions policy. In the Nash [Stackelberg] game, the fringe [coalition] countries exploit the altruism of the coalition [fringe] countries so that altruism decreases [increases] the coalition size. In any case, global emissions and global welfare are close to the non-cooperative values. However, altruism narrows the gap between the individually optimal emissions and the socially optimal emissions, so altruism increases global welfare. The effects of altruism on the formation of climate coalitions crucially depends on its modelling: If altruism affects the membership decision but not the policy decision, or if each coalition country is more altruistic toward other coalition countries than toward fringe countries, altruism can stabilise large coalitions up to the grand coalition. Finally, altruism can stabilise small coalitions but destabilises large coalitions with asymmetric countries.
Keywords: C72; D64; Q54; Q58; 330; Climate coalition; Climate policy; Moral behaviour; Social norms